Tantangan Akuntansi Dalam Pengungkapan Corporate Sosial Responsibilities dan Pembangunan Berkelanjutan - AKBAR YUSUF (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2015)
The purpose of this study to determine the accounting challenges in the disclosure of corporate socialresponsibilities and sustainable development by using a conceptual study approach. The study shows that thechallenges faced in the field of accounting for sustainable development is the complexity and uncertainty ofthe subject, which began with the absence of a clear definition to be understood about